VHF/UHF Wideband Slim Monopole Antenna with Distributed Matching Structures - Dongjie Qin; Baohua Sun (International Journal of Antennas and Propagation)
This paper presents a wideband monopole antenna with distributed matching structures operating on VHF/UHF bands. The antenna consists of a slim rectangular metal strip with a T-type slot etched on the upper half, two rectangular slots on the lower half, and two rectangular plates soldered with the bottom end of the main strip. The antenna is installed on a metal case which serves as ground. To achieve a wide bandwidth, an impedance matching network consisting of the distributed structures, which are composed of two metal plates and a metal thin strip, is devised and integrated with the main radiating strip. The T-type slot near the top tip of the main strip is used for the miniaturization of the antenna. The proposed antenna is fabricated and measured, and the measured results are in good agreement with the simulated results. The sizes of the proposed antenna and the case are 0.19λmax × 0.014λmax and 0.17λmax × 0.1λmax × 0.034λmax, respectively. The operating bandwidth is from 203.7 to 516.9 MHz (2.54 octaves) with the condition of VSWR ≤ 3 : 1. This antenna has a slim structure, a wide bandwidth covering partially VHF and UHF bands, and omnidirectional radiation patterns, so it can be the candidate for the applications of backpacked radio stations in military communication scenarios.